Serum and Salivary Level of Nitric Oxide (NOx) and CRP in Oral Lichen Planus (OLP) Patients - Atena Shiva; Shahin Arab; Seyyed Jaber Mousavi; Ali Zamanian; Avideh Maboudi (Shiraz University of Medical Sciences, 2020)
Statement of the Problem: Oral lichen planus (OLP) is a chronic inflammatory oral mucosal disease with unclear etiology while a few cases of disease become malignant. Purpose: This study aimed to evaluate the level of nitric oxide (NOx) and C-reactive protein (CRP) as oxidative stress and inflammation status in sample of OLP patients. Materials and Method: In this case-control study, serum and salivary NOx and CRP levels were evaluated in twenty two OLP patients as the case group confirmed by clinical and histopathological diagnosis, and twenty two healthy control groups collected from Tooba Oral Pathology Laboratory in Sari in 2016. The data were analyzed by using independent-samples t-test, Mann-Whitney U-test and Chi-square by using SPSS version 21. The statistical significant level was considered at p< 0.05. Results: Salivary and serum NOx levels in case group showed statistically significantly higher than healthy control group (p= 0.035 and p= 0.001, respectively). CRP values were significantly higher both in serum (p= 0.001) and in saliva (p= 0.035). A significant correlation was found between CRP and NOx values in serum (r= 0.521, p= 0.0001) and saliva (r= 0.427, p= 0.045). Conclusion: Oxidative stress causes damage to organs in the human body. Correct understanding of oxidative stress and its association with free radicals and inflammatory markers related to oral disease are important for effective treatments. The results of the study advocate the effects of NOx and CRP levels in pathogenesis of OLP. Therefore, antioxidant drugs might probably be considered in the treatment of OLP.